Contemporary clinical research of traditional Chinese medicines for chronic hepatitis B in China: An analytical review - Lingyi Zhang; Guqi Wang; Weihong Hou; Ping Li; Andrea Dulin; Herbert L. Bonkovsky (2009)
Chronic hepatitis B (CHB) is major global health problem. In China, where about 120,000,000 persons are chronically infected, CHB has been treated for centuries with traditional Chinese medicines (TCMs). This review summarizes and meta-analyzes the results of randomized controlled trials (RCTs) of TCM formulations reported in China in 1998-2008 for treatment of CHB. RCTs comparing either TCM formulations alone or in combination with interferon (IFN) or lamivudine (LAM) versus IFN or LAM were included. Chinese electronic databases were searched. The methodological quality of RCTs was assessed using the Jadad scale. TCMs had a greater beneficial effect ( P = 0.0003) than IFN and a slightly better effect ( P = 0.01) than LAM on the normalization of serum alanine aminotransferase. TCMs had a similar beneficial effect when compared with IFN or LAM for CHB on antiviral activity as evidenced by the loss of serum hepatitis B e antigen and hepatitis B virus (HBV) DNA. TCMs enhanced IFN and LAM antiviral activities and improvements of liver function. The quality of many studies was poor; reports often lacked information regarding methods of randomization or blinding and adverse events. Conclusion: Some TCMs seem effective as alternative remedies for patients with CHB, suggesting that further study of TCMs in the treatment of CHB is warranted, both in preclinical models of HBV infection and in higher quality RCTs worldwide. (Hepatology 2010;51:690–698.)